Improving the exclusionary rule: A remedial education model - Kaci, Judy Hails (American journal of criminal justice, 1988)
This article reviews the United States Supreme Court decisions on the rationale for the exclusionary rule and numerous law review articles suggesting changes in the rule. A new model is proposed to dovetail with the rule. The courts would participate in developing a compendium of rules and regulations for officers to follow in order to protect constitutional rights. Evidence would continue to be excluded if it were illegally seized in a bad faith. All officers who violate constitutional rights would be subject to remedial education. Supervisory officers and training personnel would also be responsible for the violations committed by line officers. Violations of constitutional rights would be considered when promotions and other personnel decisions are made. Lastly, the victim would be compensated by the governmental agency employing the offending officer with the agency seeking reimbursement from the employee.